Pengaruh Progressive Muscle Relaxation (PMR) Terhadap Tingkat Kelelahan Lansia Penyintas Covid 19 di Kota Pekanbaru Penelitian Dosen PemulaTahun ke 1 dari 1 - Abdurrahman Hamid; Eka Wisanti; Awaliyah Ulfah Ayudytha Ezdha (Jurnal Kesehatan Komunitas, 2023)
Introduction Fatigue is the most common symptom experienced by older adults COVID-19 survivors after fever and shortness of breath where the incidence is 30% of all older adults COVID-19 survivors. Treatment of older adults COVID-19 survivors requires an intervention that is able to accelerate the recovery of older adults from fatigue. The purpose of the study was to look at the effect of Progressive Muscle Relaxation nursing interventions on fatigue in older adults COVID-19 survivors. Methods. this study used a quasi-experimental research design with the type of pretest and posttest without a control group. By using a sample calculation of the population hypothesis test, the minimum sample size is 40 older adults. In this study, the sampling method used was multistage random sampling. The study was conducted in June-August 2022. Bivariate analysis using Paired T-Test. Results/findings The results of the study found that there was an effect of Progressive Muscle Relaxation Nursing Intervention on the fatigue level of the older adults COVID-19 survivors at Pekanbaru with a p-value of 0.001 (<0.05). This can be seen from the changes in the level of fatigue before and after the intervention. If the PMR therapy is associated with fatigue, that is, when doing this therapy, the production of endorphins, enkephalins, and serotonin releases the hormones, which will then lead to a feeling of calm and relaxation. In conclusion, this PMR Nursing Intervention can be used as an alternative form of nursing intervention to overcome fatigue problems in older adults and can be carried out by nurses in primary health care.